Safety professional's reference and study guide - Yates, W. David (Boca Raton : CRC Press, 2011)
'Written as a reference and study guide for candidates preparing to take the Board of Certified Safety Professional's exam, this book provides technical information needed for the test. It covers topics such as math review, ventilation, noise, gases and particulates, radiation, toxicology, industrial hygiene, biological hazards, thermal stressors, statistics, fire protection and prevention, accident investigation, mechanics, hydrostatics and hydraulics, electrical safety, engineering economy and worker's compensation. The book provides step-by-step instructions on how to solve the equations and formulas on the exam and gives examples on how and when to use them'--
Includes bibliographical references and index.
Keywords: Industrial safety -- Examinations -- Study guides